2006
DOI: 10.1002/mrd.20550
|View full text |Cite
|
Sign up to set email alerts
|

Generation of biologically active retro‐genes upon interaction of mouse spermatozoa with exogenous DNA

Abstract: Mature spermatozoa of most animal species can spontaneously take up foreign DNA molecules which can be delivered to embryos upon fertilization. Following this procedure, transgenic animals of various species have been generated. We recently discovered a reverse transcriptase (RT) activity in mouse spermatozoa that can reverse-transcribe exogenous RNA molecules into cDNA copies. These cDNA copies are transferred to embryos at fertilization, mosaic propagated as non-integrated structures in tissues of founder in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 37 publications
1
39
0
3
Order By: Relevance
“…It is believed that the sperm RNA is residual to spermatogenesis, and, according to this hypothesis, sperm RNA is a 'by-product' of the gradual shutdown of the nuclear transcriptional apparatus, and sperm does not support any nuclear gene transcription. However, Pittoggi and coworkers found that the transcription and splicing activities are occasionally initiated in mature sperm (Pittoggi et al 2006). Moreover, a very high abundance of sperm adhesins and most CRISP and Fn-type II mRNAs were found in ejaculated sperm, most of which exhibited weak or no expression in the testes (Song et al 2010(Song et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the sperm RNA is residual to spermatogenesis, and, according to this hypothesis, sperm RNA is a 'by-product' of the gradual shutdown of the nuclear transcriptional apparatus, and sperm does not support any nuclear gene transcription. However, Pittoggi and coworkers found that the transcription and splicing activities are occasionally initiated in mature sperm (Pittoggi et al 2006). Moreover, a very high abundance of sperm adhesins and most CRISP and Fn-type II mRNAs were found in ejaculated sperm, most of which exhibited weak or no expression in the testes (Song et al 2010(Song et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Such an effect is feasible and consistent with current models of the mammalian piRNA system if ancient bornaviruses were transmitted vertically via the gamete. Indeed, the ancient bornaviruses giving rise to EBLNs infected germ cells; otherwise a noncanonical mechanism of gene transfer from soma to germline, in violation of Weismann's law, was responsible for EBLN formation (Pittoggi et al 2006). Of note, modern bornaviruses can be transmitted vertically (Okamoto et al 2003;Kerski et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that, lacking RNA-dependent RNA-polymerases used to amplify RNAs for viral silencing in organisms for which this function is well-established (Baulcombe 2004;Rechavi et al 2011), some metazoans could use a multistep process: reverse transcription of viral transcripts followed by RNA polymerization templated on viral complementary DNA (cDNA). Sufficient reverse transcriptase activity acting on viral RNA is present in some mammalian cells to allow laboratory time-scale experiments (Pittoggi et al 2006;Horie et al 2010); LINE-1 ORF2p has recently been suggested to be the responsible enzyme in human cells (Shimizu et al 2014). While no function has been ascribed to cDNA generated by this activity in mammals, millions of years ago).…”
Section: Discussionmentioning
confidence: 99%
“…These polymerases were originally reported in human spermatozoa (and seminal plasma) back in the 1970s [43,44]. More intriguing is the more recent observation that a DNA construct containing an intronic sequence can be processed by a spermatozoal machinery such that the intron is correctly spliced out [45].…”
Section: Evidence For Latent Transcriptional Capacity In Mature Spermmentioning
confidence: 97%